Visual field changes caused by hydroxychloroquine treatment - صيادي خيريه; حبيب يوسف (Latakia University Journal -Medical Sciences Series, 2022)
Purpose:To study the effect of hydroxychloroquine on the results of visual field examination using automated perimetry(Octupus900) program G. Materials and Methods:In this cross-sectional study, the visual field of 19 patients was examined using standarded automated perimetry (Octupus900).. All patients using hydroxychloroquine for the treatment of systemic disease. fundus endoscopy are normal, intraocular pressure<16, visual acuity >1/10, no liver or renal disease. It was confirmed that all results ensure acceptable reliability indices. The presence of scotoma, its location, and the total visual field parameters (Mean Defect MD, Mean Sensitivity MS, Square root of Loss Variance SLV) were studied, and their relationship with each of the drug’s dose and duration of use was studied. Results:The visual field changes resulting from hydroxychloroquine treatment appeared as decreased sensitivity at 57.9% of the research sample, and this was confirmed by the MD value that ranged between 0.6-12.8 with an average of 4.73 ± 3.3, and The presence of scotoma was not evident on grayscale, which was by 44.7%, while it appeared on probabities more clearly , where the percentage was 71.1%, and these scotomaswere : paracentral 47.4%, central 34.2%, and peripheral 34.2%. It also found a statistically significant relationship between the duration of hydroxychloroquine treatment and these changes, where the p-value < 0.05. While there was no relationship between the dose (2.5-5.5 mg/kg) with the absence of risk factors and these changes. Conclusion:The visual field examination showed a very important role in detecting and following up the effect of hydroxychloroquine on the retina, and the changes appeared as sctomas, it was more pronounced on the probabities, in addition to the high values ​​of MD, SLV.